Exploring Antidiabetic Properties of Stingless Bee Pollen and Kasturi Mango (Mangifera casturi) Leaves: Comparative Review - Chantika Noor Khalifah; Paula Mariana Kustiawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The absence of a comparative biochemical analysis between stingless bee pollen and Mangifera casturi leaves prevents the optimization of their synergistic potential in diabetes management. This study aims to evaluate the bioactive profiles and compare the antidiabetic mechanisms of these dua natural products. The investigation utilized a systematic literature review by retrieving peer reviewed articles from PubMed, Scopus, ScienceDirect, and Google Scholar. The selection process followed the PRISMA 2020 framework to ensure a transparent and reproducible screening of literature. Data analysis involved a comparative thematic synthesis to evaluate the correlation between phytochemical groups and glycemic control. Results demonstrate that both materials share homologous flavonoid compounds that improve insulin sensitivity and mitigate oxidative stress. Stingless bee pollen provides superior pancreatic β cell protection while Mangifera casturi shows higher inhibition of carbohydrate hydrolyzing enzymes. This study concludes that both materials offer significant antidiabetic efficacy through complementary molecular pathways. These findings provide a scientific foundation for the development of evidence based complementary medicine. Future research should prioritize clinical trials to determine the optimal dosage for human application.